Tenaga Kerja Muda dan Gig Ekonomi di Asia Tenggara: Tinjauan Sistematis Literatur Tentang Peluang dan Tantangan Kebijakan (2019–2025) - Putra, Rian; Irawan, Deki; Alfisyahri, Nuriah; Ningsih, Sri (JUMANJI (JURNAL MANAJEMEN JAMBI), 2025)
The rapid expansion of the digital economy has positioned gig work as an increasingly accessible form of employment for young people across Southeast Asia. This study aims to systematically review the existing literature on the relationship between the gig economy and youth employment in the region between 2019 and 2025. Using a Systematic Literature Review (SLR) approach based on the PRISMA framework, relevant articles were identified from five major academic databases. A total of 18 articles met the inclusion criteria and were analyzed thematically. The findings reveal that gig economy platforms offer flexible opportunities and quick income for youth, particularly those excluded from formal employment. However, they also present significant challenges, including job insecurity, lack of social protection, and persistent digital inequality. The review further highlights the absence of comprehensive digital labor policies in most Southeast Asian countries and calls for adaptive regulatory frameworks that ensure fair conditions for young gig workers. This study contributes by synthesizing empirical trends and policy critiques to inform the development of inclusive and equitable labor market reforms. Its insights are relevant for policymakers aiming to promote decent work for the younger generation in the evolving digital era.